Theories of Corporate Debt Policy: A Synthesis: Discussion - Schwartz, Eduardo S. (Journal of Finance, 1979)
Eduardo S. Schwartz, Theories of Corporate Debt Policy: A Synthesis: Discussion, The Journal of Finance, Vol. 34, No. 2, Papers and Proceedings, Thirty-Seventh Annual Meeting, American Finance Association, Chicago, Illinois, August 29-31, 1978 (May, 1979), pp. 386-387